Peer Group Effects on Moslem Consumer’s Decision To Purchase Halal Labeled Cosmetics. - Muniaty Aisyah (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2015)
The purposes of this research are to analyze peer group effects on Moslem consumers’decision to purchase halal-labeled cosmetics directly and indirectly which is mediated by consumers’ religious behavior. This research applies Structural Equation Model and convenience random sampling with 215 samples who have bought halal-labeled cosmeticsand live in Southern Tangerang. The findings show that: first, peer groupdirectly affect consumers’ decisionto purchase halal-labeled cosmetics; second, hablumminannas behavior mediates peer group and consumers’decision to purchase halal-labeled cosmeticsindirectly, third, hablumminallah behavior has the most dominant effect on Moslem consumers’ decision to purchase halal-labeled cosmetics. Based on the findings, it could be concluded that the reason of consumers’ decision to purchase halal-labeled cosmetics is because their religious behavior are high. Therefore, it is suggested that government and related institutions need to implement the Security Act of Halal Products immediately in order to protect the consumer from consuming non-halal productsDOI: 10.15408/aiq.v7i2.1682